Strategic planning and its impact on the performance of business organization In accordance to shikan Insurance Company system - د شمس الدین اسماعيل محمد نور عثمان; د ابتسام محمد احمد مدني (White Nile Journal for Studies and Research, 2024)
This research is aiming into identifying the strategic planning is and its impact over working organizations performance. The research problem mainly concerned with the related impact of direct strategic plan relation with administrable operations despite the high profiled organization personnel's keep in mind the significances of strategic planning on working domain looks like. In general the strategic planning is looked whether it has significant role in rising up organization personnel's performance and efficiency. The research is significantly try to address the role of the strategic planning over type of living standards and its contribution to organizations' work. The researcher here applied the historical manual and retrieval and investigational approaches to study the phenomenon. More over the researcher depends over descriptive manual tool with support of questionnaire statistical analysis to reach for proper findings. The researcher reached up to number of findings related to the greater paid attention by the organizations high profiled personnel's to the role of the topic. They Morley concerned with the tool to take in consideration the upcoming internal and external changes. The strategic plan draws in direct attention all organization' workers to participating in its implementation at all aspects and roles. The consistently ongoing monitoring and evaluation makes possible meeting its goals and objective. Out of reached findings the researcher recommended that: Taking in consideration all choices and alternative options is very vital during strategic planning creation, this would firmly help in reaching its goal. The strategic planning document must pay more attention to look more reliable, cognitive and matching its goals and open for adequate implementation. The persistent monitoring and evaluation approaches are proved essential means for internal and external surveillance.